2019
DOI: 10.1016/j.jwpe.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the removal of oil in water emulsion by using ceramic microfiltration membrane and hybrid coagulation/sand filter-MF

Abstract: Many industries produce oil-water emulsions as major waste streams, which require specialised treatment, including the petrochemical, oil and gas and some food industries. One method to remove oil droplets from wastewater is using ceramic tubular microfiltration membranes. However, such membranes are vulnerable to fouling, which causes operational impairment. The aim of this work is to reduce ceramic membrane fouling by exploring the combination of ceramic membranes with several pre-treatment options. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The three membranes, as would be expected from Darcy's law [17,24] . Moreover, the steady-state permeate flux was always found correlate to membrane pore size.…”
Section: Effects Of Pressure On Performance Of the Ceramic Membranesmentioning
confidence: 81%
See 2 more Smart Citations
“…The three membranes, as would be expected from Darcy's law [17,24] . Moreover, the steady-state permeate flux was always found correlate to membrane pore size.…”
Section: Effects Of Pressure On Performance Of the Ceramic Membranesmentioning
confidence: 81%
“…When the TMP was increased, oil removal efficiency slightly increased due to blockage of the pores in the ceramic membrane and formation of a thicker cake layer on the membrane surface. This layer will collect oil molecules preventing passage through the membrane [17,27]. However, at higher TMP (> 2 bar), oil removal efficiency was decreased.…”
Section: Effects Of Pressure On Performance Of the Ceramic Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the total organic carbon (TOC) removal efficiency for oil-inwater emulsion was >99%. Almojjly, Johnson, Mandale, and Hilal (2019) reported that pretreatment with coagulation/sand filtration of industrial waste streams eliminated the fouling of MF membrane. Huang, Zhang, Peng, et al (2019) incorporated magnetic nanoparticles into UF membrane for the treatment of waste cutting emulsion.…”
Section: Membrane Technologymentioning
confidence: 99%
“…Outstanding properties such as excellent processability, good membrane-forming characteristics, high thermal and mechanical stability and superb chemical resistance make this polymer a promising choice for membrane applications. [1][2][3][4] So far, an extensive range of membrane related applications including ultrafiltration, 5,6 microfiltration, [7][8][9] nanofiltration, 10 membrane distillation 11 and other separation processes have been identified for the PVDF polymer. Nevertheless, PVDF membranes are often fouled by protein due to strong hydrophobicity, leading to a rapid decline in water flux.…”
Section: Introductionmentioning
confidence: 99%